EMPREENDEDORISMO: CARACTERÍSTICAS DO EMPREENDEDORISMO FEMININO NO MEIO OESTE DE SC - Silva, Bruna Rigo da; Nodari, Tânia Maria dos Santos (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2023)
The present paper aims to analyze the women entrepreneurs’ socioeconomic characteristics and skills in the west of Santa Catarina state, aiming the contribution to the development of entrepreneurial culture in this region. Based on a global analysis, due to globalization and the transformation of society in the last two decades, the presence of women has become increasingly stronger in the working market, not only in operational, but in executive level positions, such as strategic and leadership. In this regard, the proposal is to analyze businesses that are created and commanded exclusively by women in the most diverse segments in the working market, delimiting a specific study to this public located in the west of Santa Catarina state in order to identify the women entrepreneurs’ characteristics in this sector, locality and what motivates them to create their own businesses. The methodology used was quantitative and qualitative research, in order to obtain data that allows identifying the characteristics of women entrepreneurs in the delimited region, and the work points to the large and continuous growth of new businesses where a large part of these are idealized and led by women. Keywords: Women. Entrepreneurship. Culture. Business. Economy. Society.